Integrating Heterogeneous Stream and Historical Data Sources using SQL - Amará, Jefferson; Ströele, Victor; Braga, Regina; Dantas, Mário; Bauer, Michael (Journal of Information and Data Management, 2022)
Applications capable of integrating data from historical and streaming sources can make the most contextualized and enriched decision-making. However, the complexity of data integration over heterogeneous data sources can be a hard task for querying in this context. Approaches that facilitate data integration, abstracting details and formats of the primary sources can meet these needs. This work presents a framework that allows the integration of streaming and historical data in real-time, abstracting syntactic aspects of queries through the use of SQL as a standard language for querying heterogeneous sources. The framework was evaluated through an experiment using relational datasets and real data produced by sensors. The results point to the feasibility of the approach.